Implementasi Kebijakan Pengentasan Kemiskinan (Studi Kasus Rumah Padat Karya di Kelurahan Bringin, Kota Surabaya) - Dega Wahyu; Prastyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan, 2025)
Implementation of Poverty Alleviation Policy through Labor-Intensive Program in Bringin Village, Surabaya City has not been running well, several problems have been identified. Among them are declining sales turnover, lack of assistance from the Surabaya City Government and minimal assistance to support business continuity. This study aims to describe and analyze the Implementation of Poverty Alleviation Policy (Case Study of Labor-Intensive House in Bringin Village, Surabaya City). The research method used is qualitative with an intense approach and in-depth study to produce descriptive data. Data were collected through observation, interview and documentation techniques which were then analyzed using data reduction techniques, data presentation and drawing conclusions. The focus of this study uses the policy implementation model from Van Meter and Carl Van Horn. The results of the study indicate that the Labor Intensive program in Bringin Village has not been running optimally because the program standards have not been achieved, namely many business actors have closed due to the lack of visitors. Communication between organizations and business actors is less intense, the response of the Village and Sub-district seems slow in responding to the needs of business actors and the dynamics of social and economic conditions around also affect the process of program implementation is hampered. Researchers suggest providing opportunities for residents in other RW or outside the Bringin Village area to become entrepreneurs in the Bringin Labor-Intensive House, building intense and beneficial communication between regional stakeholders and business actors and creating an organizational structure led by the Head of RW and involving business actors who are still active.